Philippine medical thesaurus on anatomy fluids and secretions and stomatognathis system in Tagalog - Ragunton, Florence U.; Tarlit, Rodolfo Y. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2003)
As an initiative from the joint efforts of the Institute of Library and Information Science, University of the Philippines Diliman and the College of Medicine, University of the Philippines Manila, the creation Multilingual Philippine Medical Thesaurus Project serves as a pioneering literature for future development in Philippine medical informatics and information Science. Patterned from the Unified Medical Language System (UMLS) or the U.S. National Library of Medicine, terms were gathered from the Medical Subject Headings (MeSH) for translation to initially, the Tagalog language.
Translation of terms using the dictionaries, at the same time distributing terminology worksheets for translations to the doctors, medical practitioners, and other informants, functioned as the framework of the thesaurus. For this particular study, the researcher focused on the subcategories Fluids and Secretions and Stomatognathic System. In addition to the Tagalog equivalent of the terms, definitions of these terms were also noted and recorded, serving as the scope notes of the searched Tagalog terms. The terms from these informants were used together with the dictionary terms and definitions in the analysis and construction of index terms. Using the policies and guidelines for the translation of terms, index terms functioning as the thesaurus main entries are determined.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Filipino -- Medicine; Subject headings, Filipino -- Anatomy; Filipino language -- Medical Filipino